The Effect of Addition Superplasticizer (Sikament-LN) with Variation of Percentage on Compressive Strength Foamed Mortar Lightweight Materials - Pratama, M Ade Surya; Bermawi, Yusri; Artini, Sri Rezki; Nubli, Farhan; Pratama, Rangga Andika (CIVED, 2023)
The foamed mortar (morbus) lightweight material consists of a mixture of sand, cement, water, and liquid foam (foam agent), which can improve the mechanical properties of clay soil and increase its bearing capacity. This research uses various variations of superplasticizer mixtures, namely by adding additional ingredients in the form of sikament-LN which will increase compressive strength by up to 40% at 28 days. This research needs to be carried out to determine the effect of sikament-LN on increasing the compressive strength of foamed mortar. The percentages of the sikament-LN mixture were 0.5%, 0.75%, 1%, and 1.25% with ages of 7, 14, and 28 days, each of which made 3 test objects in 4 variations of the mixture. The research results showed that the addition of sikament-LN to the 1.25% mixture did not meet the requirements because it produced a flowability of 23.5 cm and the mixture experienced a shrinkage of > 20% when placed in a cylindrical mold. All foamed mortar specimens experienced an average dry density increase of 1.994% at a curing age of 7 to 14 days and an average dry density increase of 4.044% at a curing age of 7 to 28 days. In a mixture of 0.5%, 0.75%, and 1%, at 28 days the maximum compressive strength value obtained was 841,667 kPa (more than the required 800 kPa). For the sikament-LN mixture, a maximum of 1% of the cement weight is recommended so that the hardening process occurs in the foamed mortar test object.